PENGEMBANGAN E-MODUL BERBASIS CASE STUDY PADA MATA PELAJARAN PPKN UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PPKN - Faizah, Lailatul; Nailati, Raudah; Al-Fajri, Muhammad; A. Arif, Tarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of students' critical thinking skills in Civic Education (PPKn) indicates the need for more interactive and contextual digital learning materials. This study aimed to develop a case study-based e-module that is valid, practical, and effective in improving students' critical thinking skills in Civic Education. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included material experts, media experts, teachers, and junior high school students. The results showed that the developed e-module achieved an average validation score of 88.7%, indicating that it was highly valid. It was also considered highly practical based on teachers' and students' responses and proved effective in improving students' critical thinking skills, as indicated by an N-Gain score of 0.74, which falls into the high category. Through the use of authentic case studies related to citizenship issues, students were encouraged to analyze problems, evaluate alternative solutions, and make decisions based on the values of Pancasila. Therefore, the case study-based e-module can serve as an alternative digital learning resource that supports the implementation of the Merdeka Curriculum while fostering critical thinking skills as one of the essential competencies required in the twenty-first century.